Teachers' League of South Africa 1913-40 - Adhikari, Mohamed (Department of Historical Studies, 2016)
Besides examining the history of the Teachers' League of South Africa, a specifically coloured teachers' association, during its conservative phase from 1913 to 1940, this thesis in addition attempts to investigate the nature and development of this organization in the context of the wider social dynamic of which it was both part and product. The League is thus not only studied as a professional association but also as a specific constituent of the broader social categories of the coloured elite, the coloured people and South African society. The origins of the T.L.S.A. was rooted in the subordination of peoples of colour in Cape settler society and the development through the 19th century of a segregated education system at the Cape. More immediately, as a result of the social and political consequences of the mineral revolution intensifying racial discrimination against blacks, one of the responses of the coloured elite was the establishment of the League, through the mediation of the African Political Organisation, to protect coloured educational interests, regarded to be crucial to their advancement. The League was a typical embodiment of the assimilationist aspirations and accommodationist strategies that resulted from coloured elite marginality. This is evident in the growth and maturity of the League being largely in response to the progressive and systematic enforcement of segregation against coloureds over this period. More significantly, the League fully accepted white middle class values and codes of behaviour and its organizational life was dominated by the striving to conform to these norms. The League also displayed the essential powerlessness of the coloured elite as its representative in the tripartite contest with the Education Department and churches to influence the direction of coloured education. The interstitial position of the coloured elite in South African society was manifested by the League contradicting its basic principle of non-racism by the qualified acceptance of coloured inferiority and trying to use its closer assimilation to Western culture to claim a position of relative privilege for coloureds vis-a-vis Africans. It is apparent that at all levels of its existence the League was captive to its coloured identity and status.